Pengaruh Budaya Organisasi, Kepuasan Kerja dan Employee Engagement Terhadap Kinerja Pegawai pada UPTD Pengelolaan Prasarana Perhubungan Cilegon - Ratu Erlina Gentari; Martinus Tukiran; Annisaa Soeyono; Roosganda Elizabeth (Yayasan Literasi Sains Indonesia, 2023)
This study aims to determine the effect of the organizational culture, job satisfaction and employee engagement on employee performance at UPTD pengelolaan prasarana perhubungan (Dinas Perhubungan Kota Cilegon). The method used is a quantitative method. The sample selection technique used a saturation sampling method where all members of the population were sampled, amounting to 56 respondents. The statistical methods used are normality test, multicolliniearity test, hetesscedasticity test, correlation coefficient test, R2 test ( coefficient of determination), multi linier regression analysis. The results of the t-test in this study indicate that organizational culture has not significant on employee performance, the results of the t-test in this study indicate job satisfaction has a significant effect of employee performance, the results of the t-test in this study indicate that employee engagement has a significant on employee performance. The results of the F-test show that the level of all variables is high. It can be concluded that the organizational culture, job satisfaction and employee engagement simultaneously have a positive and significant effect on employee performance at UPTD pengelolaan prasarana perhubungan.